Untreated, urea-enriched and thermal-ammoniated oat grain as supplementary feed for pregnant and lactating South African Mutton Merino ewes grazing wheat stubble - Brand,T.S.; Brand, A.A.; Cloete, S.W.P. (1992)
Plain (OAT), 1.4% urea-enriched (EOAT) and 3% themal-ammoniated (NH3OAT) oat grain were fed to South African Mutton Merino ewes as supplementary feed during late pregnancy and lactation, while grazing wheat stubble at 2 ewes/ha during 1986 and 1987. Blood glucose, urea, calcium, magnesium and zinc levels of the ewes were monitored in 1986 only. Ewes received supplementary feed at 750 g/ewe/d for 16 weeks in 1986, and 550 g/ewe/d for 10 weeks and 750 g/ewe/d for the subsequent 6 weeks in 1987. The crude protein (CP) content of the oats was increased from 9.8% to 12.5% (EOAT) and 15.8% (NH3OAT) in the first year and from 8.7% to 11.7% (EOAT) and 13.0% (NH3OAT) in the second year. Ewes which received EOAT and (NH3OAT) grain as supplement, tended in both years to maintain higher mean live masses (P